Reunión de un grupo pequeño de personas. (UNED, 2023)
Aparece de izquierda a derecha: Juan Humberto Cevo Guzmán, Jorge Enrique Guier Esquivel, Francisco Antonio Pacheco Fernández - Rector, Enrique Góngora Trejos